Sistem Pendukung Keputusan Penilaian Kualitas Jasa Hotel dengan Mengimplementasikan Metode Analytical Hierarchy Process (AHP) - Hersatoto Listiyono; Muhammad A.R. Hidayat; P Purwatiningtyas; Eko Nur Wahyudi (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
It is time for hotels to use advances in computer technology, both software and hardware, in an effort to handle management, which was previously done manually. One of them is the assessment of the quality of services at hotels because later the ratings from visitors can become a reference for improving the quality ofservices at hotels. This study aims to create an application program for assessing the quality of hotel services, with anapplication program for assessing the quality of hotel services, it will help hotel management in improving hotel services to the fullest. In this service quality assessment application program, theAanalytical Hierarchy Process method is used to determine the valueofthe weightof the criteria. The endresultofthis research is a service quality assessment application program where the result of the program is a recapitulation of hote lservice quality assessment